New era of education: mobile learning of coronary guidewires in cardiovascular medicine. (14th October 2021) - Kyaw, H; Vengrenyuk, A; Johal, G; Goel, S; Sharma, S; Kini, A
Abstract: Background: Online education has transformed the way we teach and learn, especially in the midst of a global pandemic. Multiple devices, including coronary guidewires, are required to perform a successful coronary intervention, and understanding the engineering aspect of coronary guidewire technology is paramount. Purpose: We aim to develop and evaluate a novel teaching tool/mobile learning app to understand a complex guidewire architecture and appropriate wire selection based on a lesion characteristics. Methods: A guidewire is incredibly complex, consisting of a multitude of technologies allowing a range of tip softness, trackability around curves, and precise torque control. Despite operator preference, the process of choosing an appropriate coronary guidewire has gone mostly unchanged. We envisioned developing the GuidewireAID app with three main parts: 1) wire basics, 2) lesion-based guidewire selection, and 3) cased-based approach. Appropriate teaching cases were selected from a large-volume catheterization laboratory and divided into non-chronic total occlusion (non-CTO) and CTO. Non-CTO cases include simple, calcified, angulated, and bifurcation lesions, as well as thrombotic occlusion and tortuous vessels (Figure 1). Each case is described and analysis is offered on how to select an appropriate wire, followed by teaching points pertinent to the topic. Results: Twenty-three detailed clinical cases and more than a hundred wires are illustrated in the GuidewireAID app. Case presentation, angiographic analysis, and a thorough understanding of wire characteristics allows the operator to know which wire to use and when it is time to switch, especially when dealing with complex coronary cases. Conclusion: The GuidewireAID app will help fellows in training (FIT), early career interventionists, and practicing interventional cardiologists understand the complex aspects of a coronary guidewire and appreciate how their nuances could overcome real-world clinical challenging scenarios. FUNDunding Acknowledgement: Type of funding sources: None.